The potential endocrine-disrupting of fluorinated pesticides and molecular mechanism of EDPs in cell models - Yalan Liu; Fengzhong Wang; Lin Li; Bei Fan; Zhiqiang Kong; Jianxin Tan; Minmin Li (Ecotoxicology and Environmental Safety)
Environmental endocrine disruptors constitute a category of exogenous compounds that interfere with the endocrine system's functions in organisms or cells. As a class of particularly representative endocrine-disrupting chemicals, the accumulation of per- and polyfluoroalkyl substances potentially leads to adverse health effects, including hormonal disruptions, developmental issues, and cancer. However, the classification of these disruptors is intricate, and the data on their potential health risks is scattered. The research into fluorinated pesticides is somewhat superficial, with the majority of review articles in this field focusing on the structural characteristics, biodegradation processes, and environmental risks associated with these pesticides. In this study, we compared and investigated the research development processes of seven types of fluorine-containing pesticides and five types of fluorinated endocrine disruptors. The varying toxic effects of these endocrine disruptors are highly dependent on exposure conditions. Their actions are complex, affecting behavioral substances throughout the organism, and monitoring some complex biological phenotypes, sex- or age-specific effects, and behavioral learning poses significant challenges. The findings will serve as a reference for future studies on the toxicity of pesticides to humans and other organisms.